2012
DOI: 10.3390/molecules171011484
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant and Anti-inflammatory Effects of Phenolic Compounds Isolated from the Root of Rhodiola sachalinensis A. BOR

Abstract: Isolation of compounds from the root of Rhodiola sachalinensis (RRS) yielded tyrosol (1), salidroside (2), multiflorin B (3), kaempferol-3,4′-di-O-β-D-glucopyranoside (4), afzelin (5), kaempferol (6), rhodionin (7), and rhodiosin (8). Quantification of these compounds was performed by high-performance liquid chromatography (HPLC). To investigate the antioxidant and anti-inflammatory effects of the compounds, DPPH radical scavenging, NBT superoxide scavenging and nitric oxide production inhibitory activities we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 21 publications
(24 reference statements)
2
43
0
1
Order By: Relevance
“…Similarly, the crude methanol and water extracts also displayed considerable amount of phytochemical constituents viz., phenolics, tannins, flavonoids, ascorbic acid and saponins depending upon the extractive capacity of the solvents ( Table 2). The above findings were in concordance with the reports of Choe et al [38] and Pirbalouti et al [39] who found that the phenolic and flavonoid contents were generally higher in high polar solvents. Therefore, it is apparent that methanol was the most effective solvent in the extraction of bioactive compounds from the crude samples.…”
Section: Resultssupporting
confidence: 83%
“…Similarly, the crude methanol and water extracts also displayed considerable amount of phytochemical constituents viz., phenolics, tannins, flavonoids, ascorbic acid and saponins depending upon the extractive capacity of the solvents ( Table 2). The above findings were in concordance with the reports of Choe et al [38] and Pirbalouti et al [39] who found that the phenolic and flavonoid contents were generally higher in high polar solvents. Therefore, it is apparent that methanol was the most effective solvent in the extraction of bioactive compounds from the crude samples.…”
Section: Resultssupporting
confidence: 83%
“…Tyr is a natural antioxidant that displays various properties, including anti-oxidant and anti-inflammatory properties. 12) In the present study, we found that Tyr had a protective effect on LPS-induced ALI and identified some of the underlying mechanisms for this.…”
Section: Discussionmentioning
confidence: 62%
“…[9][10][11] Tyr has been reported to have many pharmacological properties, including cardioprotective, anti-oxidant and anti-inflammatory effects. 10,12,13) Emerging evidence has shown that Tyr can also suppress the inflammatory response and oxidative stress by reducing the production of inflammatory mediators in vitro, probably via inhibition of the NF-κB and MAPKs signal pathways. [14][15][16] Through rodent models, Tyr was demonstrated to attenuate the pulmonary edema induced by hypobaric hypoxia.…”
Section: )mentioning
confidence: 99%
“…여기서 salidroside는 여정실에서는 처음으로 분리되었다. 문헌에 보고된 바에 의하면 tyrosol은 아미노산인 타이로신으로부 터 카복실기가 제거되어 생성된 물질이며 지중해 식단을 구성하는 올리브 오일의 주요한 페놀 구성성분들중에 하 나로서 과거 수 십년 동안 항미생물, 항트롬빈, 항염증, 심 장보호 등과 같은 다양한 생리활성으로 주목을 받았다 (Gris et al 2011;Choe et al 2012;Vlachogianni et al 2015;Antenucci et al 2016). Phenylpropanoid glycoside 인 salidroside는 이전에 참돌꽃(Rhodiola sachalinensis), 산청목(Acer tegmentosum) 등으로부터 분리되었으며 (Kim et al 2004;Lee et al 2014), 항암, 항염증, 항저산소증, Means with the different letters at the same concentration are significantly different (P < 0.05) by Duncan's multiple range test.…”
Section: A-kunclassified